Analysis of Language Politeness of Medan State University Physics Students - Vebri Filiandi; Dina Yulpiani; Chairiyah, Muti Amanda; Lasenna Siallagan; Ranap Fransiskus Togatorop; Yenni Enjelina Simatupang (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2024)
This research aims to analyze language politeness. Language politeness is a key aspect in academic communication, reflecting cultural values ​​and social norms. This research uses a qualitative descriptive approach with a questionnaire as a data collection method. The results show that the majority of respondents consider the importance of language politeness in interactions, but there are also concerns about the lack of attention to politeness. It was found that a lack of language politeness can harm the university's image. This study increases understanding of the importance of politeness in academic contexts, especially at Medan State University.